Arabidopsis Kunitz Trypsin Inhibitors in Defense Against Spider Mites - Arnaiz, Ana; Talavera-Mateo, Lucia; Gonzalez-Melendi, Pablo; Martinez, Manuel; Diaz, Isabel; Santamaria, M. E. (Frontiers in Plant Science, 2018)
Tetranychus urticae (two-spotted spider mite) is a striking example of polyphagy among herbivores with an extreme record of pesticide resistance and one of the most significant pests in agriculture. The T. urticae genome contains a large number of cysteine- and serine-proteases indicating their importance in the spider mite physiology. This work is focused on the potential role of the Kunitz trypsin inhibitor (KTI) family on plant defence responses against spider mites. The molecular characterization of two of these genes, AtKTI4 and AtKTI5, combined with feeding bioassays using T-DNA insertion lines for both genes was carried out. Spider mite performance assays showed that independent KTI silencing Arabidopsis lines conferred higher susceptibility to T. urticae than WT plants. Additionally, transient overexpression of these inhibitors in Nicotiana benthamiana demonstrated their ability to inhibit not only serine- but also cysteine-proteases, indicating the bifunctional inhibitory role against both types of enzymes. These inhibitory properties could be involved in the modulation of the proteases that participate in the hydrolysis of dietary proteins in the spider mite gut, as well as in other proteolytic processes.